Sister Septuagint Virginal Allusions as Textual Apologetic in De vita Mosis - Sieber, Julian J. (2025)
In this essay, I examine Philo's description in De vita Mosis of the Septuagint as sister, ἀδελφή, to the Hebrew Mosaic Law as a pointedly feminine figure of speech. The metaphor is in some ways similar to the gendered and sexualized notions of textual purity that undergird modern textual criticism. At the same time, the consistent use of gender across the works of Philo is an important ideological context that complicates the consideration of the translation narrative through a purely genealogical conception of textual transmission. I argue that Philo presents the Septuagint as not only conspicuously feminine but also as specifically virginal to stress its nature as pure while also in danger of being viewed as corrupted. In doing so, Philo uses contemporaneous conceptions of gender to strengthen an apologetic narrative defending the divinity of both Moses the lawgiver and the translation of the Greek text he spent his life expounding.
Keywords: De vita Mosis; Philo of Alexandria; Gender; Textual Criticism